TELAAH HUKUM EKONOMI SYARIAH DALAM PEMIKIRAN IBNU TAIMIYAH - Mu'adil Faizin (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
The role of the state in the economic growth of society can never be ignored. There is a strategic role of the state to regulate wealth nationally, to distribute wealth to all those in need. Something most people don't realize. Sheikh al-Islam Ibn Taimiyah in addition to producing works in the field of economics. His thoughts came to examine the fundamental role of the state in the economy. Ibn Taimiyah seemed to formulate the relationship between the state and the practice of sharia economics, the position of the state became closer in supervising the practice of muamalah. Based on the description above, this paper discusses Ibn Taimiyah's economic thought, in terms of its rationalization, to the strategic steps found.